2013
DOI: 10.1029/me004p0001
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Seismicity Patterns Before Large Earthquakes

Abstract: Abstract. Various seismicity patterns before major earthquakes have been reported in the literature. They include foreshocks (broad sense), preseismic quiescence, precursory swarms, and doughnut patterns. Although many earthquakes are preceded by all, or some, of these patterns, their detail differ significantly from event to event. In order to examine the details of seismicity patterns on as uniform a basis as possible, we made space-time plots of seismicity for many large earthquakes by using the NOAA and JM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(82 citation statements)
references
References 57 publications
6
66
0
1
Order By: Relevance
“…This is reminiscent of the natural phenomenon of seismic quiescence, i.e. a period of greatly reduced seismicity observed before certain large earthquakes (Habermann 1988;Kanamori 1981;Sobolev 2011).…”
Section: Discussionmentioning
confidence: 99%
“…This is reminiscent of the natural phenomenon of seismic quiescence, i.e. a period of greatly reduced seismicity observed before certain large earthquakes (Habermann 1988;Kanamori 1981;Sobolev 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (Evison, 1977;Mogi, 1977;Kanamori, 1981;Singh and Singh, 1984;Ohtake et al, 1977;Gupta and Singh, 1989;Shanker et al, 1995Shanker et al, , 2010Singh et al, 2005;Paudyal et al, 2009) have have suggested that seismicity preceding major earthquakes could be defined by the following episodes: (1) background/normal seismicity, (2) precursory swarm, (3) quiescence, (4) foreshocks and (5) mainshock. In most of the anomalous sequences, the magnitude of mainshocks observed to be 1-2 units higher than the magnitude of the largest swarm event (Evison, 1977;Singh et al, 1982Singh et al, , 2005Shanker et al, 1995).…”
Section: Discussionmentioning
confidence: 98%
“…The parameter 'b' depends on the effective stress regime and tectonic character of the region (Hatzidimitriou et al 1985;Tsapanos, 1990). Decreasing of 'b' value within seismogenic volume correlates the increasing effective stress levels prior to a major shock (Kanamori, 1981) or increase in applied shear stress / effective stress (Urbancic et al 1992). Smith (1986) observed that the Cape Campbell earthquake of January 1977 was preceded by and located close to a high b-value.…”
Section: B-value In the Clustersmentioning
confidence: 93%